How Organizational Climate Influences Innovation: A Qualitative Inquiry into the Commerce Sector - Mosafer, Leila; Bakhshayesh, Saba; Dilmaghani, Saeeid; Falsafi Fard, Mona (Management Strategies and Engineering Sciences, 2024)
Methodology: A qualitative research design was employed, using semi-structured interviews with 21 professionals in Tehran’s commerce sector. Purposeful sampling ensured the inclusion of participants with direct experience in organizational innovation. Interviews continued until theoretical saturation was reached, capturing diverse perspectives. Thematic analysis was conducted using NVivo software, identifying key themes and subthemes that explain the influence of organizational climate on innovation. The study identified four main themes: leadership and management practices, work environment and resources, employee engagement and collaboration, and organizational support for innovation. Visionary leadership, effective communication, and resource allocation emerged as critical enablers of innovation. Employee engagement strategies, such as team dynamics and recognition mechanisms, also played a pivotal role. Barriers to innovation included insufficient resources and resistance to change. The findings align with previous studies, emphasizing the importance of a supportive and collaborative climate in fostering innovation. The study highlights the multifaceted role of organizational climate in shaping innovation within the commerce sector. Leadership styles, resource management, and employee engagement are critical drivers of innovation. Organizations should prioritize creating a positive climate by investing in leadership development, enhancing resource accessibility, and fostering a culture of collaboration and recognition. These strategies can enable organizations to remain competitive in rapidly changing markets.